Consumption of fruits and vegetables among individuals 15 years and older in 28 low- and middle-income countries - Frank, Sarah; Webster, Jacqui; McKenzie, Briar; Geldsetzer, Pascal; Manne-Goehler, Jennifer; Andall-Brereton, Glennis; Houehanou, Corine; Houinato, Dismand; Gurung, Mongal Singh; Bicaba, Brice Wilfried; McClure, Roy Wong; Supiyev, Adil; et al. (The journal of nutrition, 2019)
The WHO recommends 400 g/d of fruits and vegetables (the equivalent of ∼5 servings/d) for the prevention of noncommunicable diseases (NCDs). However, there is limited evidence regarding individual-level correlates of meeting these recommendations in low- and middle-income countries (LMICs). In order to target policies and interventions aimed at improving intake, global monitoring of fruit and vegetable consumption by socio-demographic subpopulations is required. Objectives: The aims of this study were to 1) assess the proportion of individuals meeting the WHO recommendation and 2) evaluate socio-demographic predictors (age, sex, and educational attainment) of meeting the WHO recommendation. Methods: Data were collected from 193,606 individuals aged ≥15 y in 28 LMICs between 2005 and 2016. The prevalence of meeting the WHO recommendation took into account the complex survey designs, and countries were weighted according to their World Bank population estimates in 2015. Poisson regression was used to estimate associations with socio-demographic characteristics. Results: The proportion (95% CI) of individuals aged ≥15 y who met the WHO recommendation was 18.0% (16.6–19.4%). Mean intake of fruits was 1.15 (1.10–1.20) servings per day and for vegetables, 2.46 (2.40–2.51) servings/d. The proportion of individuals meeting the recommendation increased with increasing country gross domestic product (GDP) class (P < 0.0001) and with decreasing country FAO food price index (FPI; indicating greater stability of food prices; P < 0.0001). At the individual level, those with secondary education or greater were more likely to achieve the recommendation compared with individuals with no formal education: risk ratio (95% CI), 1.61 (1.24–2.09). Conclusions: Over 80% of individuals aged ≥15 y living in these 28 LMICs consumed lower amounts of fruits and vegetables than recommended by the WHO. Policies to promote fruit and vegetable consumption in LMICs are urgently needed to address the observed inequities in intake and prevent NCDs.Background: The WHO recommends 400 g/d of fruits and vegetables (the equivalent of ∼5 servings/d) for the prevention of noncommunicable diseases (NCDs)